Reporting on Labour: Class Consciousness ond the Uncertain Ideological Boundaries of Canadian Journalism - Costain, Gene (Javnost-The Public, 2005)
One of the central questions in this study was whether a group of mainstream labour reporters could create a culture of resistance in their journalism practice. This research also tested a dual conception of the group as an interpretive community and a culture of dissent, rather than as just members of a profession adhering to the rigidities of their professional roles in the mainstream press. The goal in this study was to shed light on the reporters’ unique roles during a specific period of change, and to view them as interpreters of unfolding social events during a time of significant political change.